2019
DOI: 10.1007/s11356-019-04542-2
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological assessments of biochar additions to soil employing earthworm species Eisenia fetida and Lumbricus terrestris

Abstract: Biochar is the degradation-resistant product generated by the pyrolysis of organic materials and is produced for the intended use of land application in order to promote carbon sequestration and soil improvement. However, despite the many potential benefits biochar application offers, it is important to quantify any ecological impacts that may result from soil amendment in order to avoid potentially causing negative effects upon soil biota which are crucial in the many ecosystem services provided by soil. Any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…These results highlight that the use of biochar for soil restoration may reduce the chance of PTEs entering the terrestrial food web through earthworms, if they are predated by higher animals (i.e. mammals, birds, reptiles and amphibians) (Elliston and Oliver, 2020). Only Sb-BAF increased for earthworms grown in the amended soils (i.e.…”
Section: Ptes Concentration and Bioaccumulation In E Fetida And Acute...mentioning
confidence: 87%
“…These results highlight that the use of biochar for soil restoration may reduce the chance of PTEs entering the terrestrial food web through earthworms, if they are predated by higher animals (i.e. mammals, birds, reptiles and amphibians) (Elliston and Oliver, 2020). Only Sb-BAF increased for earthworms grown in the amended soils (i.e.…”
Section: Ptes Concentration and Bioaccumulation In E Fetida And Acute...mentioning
confidence: 87%
“…In aquatic ecosystems, biochar was shown to increase the leaching of dissolved organic carbon, and this apparently reduced the light penetration in lakes [131,191]. Finally, studies have shown that biochar application disturbed the abundance of earthworms (Lumbricus terrestris), which play a key role in soil formation, breakdown of organic matter, and nutrient cycling in agroecosystems [192].…”
Section: Limitation Of Biochar Application On Soil and Potential Risksmentioning
confidence: 99%
“…As such, changes in metrics like reproduction, mortality, growth, and behaviour are easy to test experimentally, making E. fetida an ideal candidate for examining the potential lethal and sublethal effects of environmental contaminants. To date, E. fetida have been used to examine the effects of many potential environmental contaminants, including compounds like heavy metals, pesticides, and artificial soil (Yasmin & D'Souza, 2007;Garcia-Velasco et al 2017;Elliston & Oliver, 2019). Although some studies have tested the effects of various applications of C. sativa on E. fetida and found that there are no short-term lethal effects (Chauhan & Joshi, 2010;Benelli et al 2018), potential sublethal effects on reproduction, growth, and behaviour remain unknown.…”
Section: Earthworms As a Terrestrial Study Organismmentioning
confidence: 99%